Struggling Against Radicalism Through the Sunnah of the Prophet Muhammad SAW. - Ali Mohtarom (LP2M Universitas Ibrahimy, 2023)
Citing a hadith from the Prophet Muhammad SAW, this essay discusses how radicalism is handled in Indonesia as an extremist and terrorist problem. Using the Integrative Review paradigm, it uses a qualitative approach and literature review as its research technique. The Hadith of the Prophet provides two strategies: preventative activity and repressive action. Promoting attitudes of moderation, tolerance, compassion, justice, equality, and prudence while issuing fatwas are examples of preventive efforts. Repressive measures, on the other hand, are meant to deal with hypocrites and Khawarij to preserve the Muslim Ummah's unity and defend the Muslim community's wellbeing per the hadith recorded in Sahih Bukhari and Sahih Muslim.